Silent Letter Pronunciation Errors Made by English Major Students of Raden Intan State Islamic University - Kurniawan, Iwan; Aghisnandea, Dhea; Isnaini, Rahmi (Universitas Islam Negeri Raden Intan Lampung, 2022)
The purposes of this research were to classify the types of error made by the students in pronouncing silent letter, to count the total of errors that students made, and to know the source of errors. The subjects of the research were the students at the second semester of English Education Raden Intan State Islamic University of Lampung. The H class of the afforementioned students were the sample and purposing sampling technique was used to sample that class of 29 students. The result of the research showed that there were 4 types of errors; omission, addition, misformation, and misordering. The total of errors were 343 error’s items which made by the students. Addition was the most common errors made by the students, which was 211 items or 61,51%. Second most common was misformation with 84 items or 24,48%. It then followed by omission with 46 items or 13,41%. At the end of the errors’ classification based on surface strategy taxonomy was misordering with 2 items or 0,58%.